Highly tunable dual bound states in the continuum in bulk Dirac semimetal metasurface. (10th March 2021) - Ma, Changchun; Lin, Qi; Wang, Lingling; Huang, Kai
Abstract: We present a bulk Dirac semimetal (BDS) metasurface to realize tunable dual bound states in the continuums (BICs). The dual polarization-dependent BICs can transform into quasi-BICs with EIT or Fano lineshapes by breaking the structural symmetry. The excitation of quasi-BICs can attribute to the coupling between magnetic quadrupole mode and electric dipole mode (quasi-BIC I), or the coupling of two magnetic quadrupole modes (quasi-BIC II). The BIC resonant wavelength can be dynamically tuned while maintaining the spectral lineshape by varying the Fermi energy of BDS without re-optimizing the geometrical structures, which provides a new route for ultra-compact active BIC device.